Surface modification of steel R6M5 under the effect of supercurrent ion beams - Asainov O. Kh.; Didenko A. N.; Krivobokov V. P. Valery Pavlovich; Pogrebnyak A. D.; Ruzimov Sh. M. (1985, 1985)
X-ray crystallographic and metallographic analysis and electron-positron annihilation were used to investigate peculiarities of the effect of supercurrent ion beams of nanosecond length on the structure of steel R6M5. An austenite layer 1-7 mu m deep forms on the surface. Profiles of the structure function near the surface obtained from analysis of the angular distribution of annihilation photons indicate that there is a change in the crystal lattice at a depth below the ionic path length.